Implementation of Accounting Information Systems in the Tiumnon Farmer Group - Maria Prudensiana Leda Muga; Melianus Efritron Tkela (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to analyze the SIA of the Tiumneno Farmers' Group and analyze the readiness of the Human Resources (HR) of the Tiumnon Farmers' Group to face the era of society 5.0. This research approach uses a qualitative descriptive analysis regarding the implementation of SIA in farmer groups. The results of this research are the design of the Tiumnon Farmers Group Accounting Information System (SIA) in the form of a financial application and the members of the Tiumnon Farmers Group are ready to face the era of society 5.0 and have leadership skills and IT literacy. However, the Tiumnon Farmers Group must still be assisted and given ongoing training.